The Existence of the Corruption Eradication Commission Leadership in Investigations After the Enactment of Law Number 19 of 2019 - Ahmad Sahroni (Dinasti Research, 2024)
This study aims to show how the existence of the KPK Leadership as investigators after the enactment of Law Number 19 of 2019 and what its implications are. The preparation of this research was carried out using the type of Normative Juridical research with a statute-approach, conceptual approach and case approach. Based on the research conducted, the authority of the KPK Leadership as investigators has been lost since the enactment of Law Number 19 of 2019 and has had an impact on the failure to realize legal certainty in handling corruption cases, especially in the investigation process. By understanding the concept of authority based on the principle of legality, and by comparing the regulation of authority in the KPK Law and the Prosecutor's Law, it can be seen that regulations must be written clearly in accordance with the principle of lex scripta. It is necessary to carry out reconceptualization and written regulations related to the authority of the KPK Leadership. This research is expected to be able to provide insight to the public and can be a reference for everyone to realize legal certainty, justice and benefits, especially in handling corruption cases.